THE INFLUENCE OF RELIGIOSITY ON TAX COMPLIANCE IN NIAS ISLAND:THE MODERATING ROLE OF TAX KNOWLEDGE AND THE MEDIATING ROLE OF TAX AWARENESS: INTRODUCTION - Reaksi Zagoto; Anskaria Simfrosa Gohae (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Abstract This study analyzes the influence of religiosity on tax compliance with the moderating role of tax knowledge and the mediating role of tax awareness in the community of Nias Island. Using the Structural Equation Modeling Partial Least Squares (SEM-PLS) approach, the results show that religiosity is an important determinant that drives intrinsic moral motivation to fulfill tax obligations voluntarily and ethically. Religiosity also increases tax awareness by internalizing fiscal obligations as a moral responsibility, strengthening civic engagement based on spiritual values. Tax awareness is found to be the main factor encouraging compliance, with conscious recognition of the social function and development role of taxes. In contrast, tax knowledge does not play a significant role as a moderating variable in the relationship between religiosity, awareness, and compliance. These findings indicate that moral mechanisms and awareness are more dominant than technical understanding in shaping taxpayer behavior. Furthermore, tax awareness mediates the influence of religiosity on compliance, reinforcing the importance of moral and spiritual values in promoting compliant behavior. The practical implications emphasize the need for developing tax education and policies focused on moral and awareness-based approaches.